Pierre e Paul, i dettagli del sentimento. Postilla sul bergsonismo di Pierre Menard - Rinaldo Rinaldi (Parole Rubate, 2020)
This essay focuses on the relationship between Jorge Luis Borges’s idea of literature and Henri Bergson’s philosophy. Examining a passage from the latter’s "Essai sur les données immédiates de la conscience" (1889), this article suggests a possible resemblance to (but also a provocative subversion of) Borges’s 1939 famous tale, "Pierre Menard, autor del Quijote".